2019
DOI: 10.1007/978-3-030-27477-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Multi Agent System for Machine Learning Under Uncertainty in Cyber Physical Manufacturing System

Abstract: Recent advancements in predictive machine learning has led to its application in various use cases in manufacturing. Most research focused on maximising predictive accuracy without addressing the uncertainty associated with it. While accuracy is important, focusing primarily on it poses an overfitting danger, exposing manufacturers to risk, ultimately hindering the adoption of these techniques. In this paper, we determine the sources of uncertainty in machine learning and establish the success criteria of a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For instance, an interpolating agent only needs to be present in the chain if some later step requires equidistant data. An agent framework that is designed with metrological use cases in mind is the Python package agentMET4FOF 0.4.1 [13]. The following example is implemented using this framework.…”
Section: Extending Digital Sensors To Smart Traceabilitymentioning
confidence: 99%
“…For instance, an interpolating agent only needs to be present in the chain if some later step requires equidistant data. An agent framework that is designed with metrological use cases in mind is the Python package agentMET4FOF 0.4.1 [13]. The following example is implemented using this framework.…”
Section: Extending Digital Sensors To Smart Traceabilitymentioning
confidence: 99%
“…Yong et al have presented a demonstrator system for using the sensor agents to improve the handling of uncertainty in predictive ML in a cyber-physical manufacturing system (CPMS) [ 35 ]. ML has become more and more popular in optimizing operations and processes in manufacturing and quality control as it can effectively be used, for example, in predictive maintenance.…”
Section: Related Workmentioning
confidence: 99%
“…The idea behind IIoT is that it enables an increased level of automation and better overall understanding of processes, leading to improved efficiency and thus profitability. In smart factories and manufacturing, sensor networks are used to provide data for ML applications, cyber-physical systems, and digital twins, for example, for managing manufacturing processes or supply chains [ 2 , 35 , 55 , 56 ]. Such applications provide frameworks for predictive analysis for maintenance, prognostics, and decision-making.…”
Section: Use Case Examplesmentioning
confidence: 99%
“…The digital twins and the social platform are implemented for experiments discussed here and are therefore briefly described in the following paragraphs. A detailed description of the overall architecture and industrial multi‐agent systems, in general, can be found in [8, 16, 34, 35], respectively. The notion of agents’ in this paper refers to a collection of computational entities, that cooperate or compete to achieve a certain objective [36].…”
Section: Implementing Fedavg For Prognosismentioning
confidence: 99%